1962
DOI: 10.1080/00268976200100261
|View full text |Cite
|
Sign up to set email alerts
|

The electron spin resonance spectra of CH(SO3)2=and N(SO3)2=

Abstract: The electron spin resonance spectra of the radical CH(SOs)2 = trapped in a single crystal of potassium methane disulphonate and of the isoelectronic radical N(SO3)2 = in the isostructural potassium amine disulphonate crystal are interpreted. The hyperfine couplings for H, 13C and 14N nuclei and the g-factors are given. The unpaired electron occupies a :r-orbital of predominantly central-atom 2p character in each case. The spin populations are derived. An unusual feature, prominent in the potassium methane disu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1962
1962
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Although the elements of the several proton A-tensors could not be determined the principal g-values (Table 1) are those of a typical carboncentered n-radical. It should be noted that the proximity of the sulfur in an -SO3-group, attached to the carbon in question would not be expected to be reflected in the g-tensor values since in the radical CH(S03-), the principal values are 2.0033, 2.0025, and 2.0019 (9).…”
Section: Resultsmentioning
confidence: 99%
“…Although the elements of the several proton A-tensors could not be determined the principal g-values (Table 1) are those of a typical carboncentered n-radical. It should be noted that the proximity of the sulfur in an -SO3-group, attached to the carbon in question would not be expected to be reflected in the g-tensor values since in the radical CH(S03-), the principal values are 2.0033, 2.0025, and 2.0019 (9).…”
Section: Resultsmentioning
confidence: 99%
“…The negative sign of the isotropic hfs is inferred on this basis. The isotropic splitting from a unit 2s density for 14N has been estimated [62], and the corresponding value for ' 5 N may be deduced with the ratio of their respective nuclear moments. The experimental isotropic component corresponds to p2 = 0.026.…”
Section: Ligand Nitrogen Endormentioning
confidence: 99%
“…The aaso a-lines can be seen, as well as the 13CH(SO3-)2 lines discussed in the following paper [9]. To first order the azSO 3-line should lie at the centre of the four equally spaced lines of aaSOa-.…”
Section: Optical Measurementsmentioning
confidence: 98%
“…The results are summarized in table 1. The electron resonance measurements showed that more than one radical is produced in each case, some of which have been identified [9,10]. The spectra all had one feature in common, a line with a nearly isotropicg-factor of 2.004 which was assumed to be due to azSO3-.…”
Section: Optical Measurementsmentioning
confidence: 99%